Psychotropic drugs in Nepal: perceptions on use and supply chain management - Nawaraj Upadhaya; Mark J. D. Jordans; Dristy Gurung; Ruja Pokhrel; Ramesh P. Adhikari; Ivan H. Komproe (BMC, 2018)
Abstract Background Psychotropic drugs play an important role in the treatment of mental, neurological and substance use disorders. Despite the advancement of the use of psycho-pharmaceuticals in the developed countries, the psychotropic drug production and supply chain management in low- and middle- income countries are still poorly developed. This study aims to explore the perceptions of stakeholders involved in all stages of the psychotropic drug supply chain about the need, quality, availability and effectiveness of psychotropic drugs, as well as barriers to their supply chain management. The study was conducted among 65 respondents from the Kathmandu, Chitwan and Pyuthan districts, grouped into four categories: producers, promoters and distributors (N = 22), policy makers and government actors (N = 8), service providers (N = 21) and service users/family members (N = 14). Results The respondents reported that psychotropic drugs, despite having side effects, are 1) needed, 2) available in major regional centers and 3) are effective for treating mental health problems. The stigma associated with mental illness, however, forces patients and family members to hide their use of psychotropic drugs. The study found that the process of psychotropic drug supply chain management is similar to other general drugs, with the exceptions of strict pre-approval process, quantity restriction (for production and import), and mandatory record keeping. Despite these regulatory provisions, respondents believed that the misuse of psychotropic drugs is widespread and companies are providing incentives to prescribers and retailers to retain their brand in the market. Conclusions The production and supply chain management of psychotropic drugs is influenced by the vested interests of pharmaceutical companies, prescribers and pharmacists. In the context of the government of Nepal's policy of integrating mental health into primary health care and increased consumption of psychotropic drugs in Nepal, there is a need for massive education and awareness as well as strict monitoring and supervision to avoid the misuse of psychotropic drugs.